An evaluation of the performance management and development system of the Eastern Cape Department of Health - Javu, Mncedi Gladman (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
This study used a quantitative approach to evaluate the application of the performance management and development system in the Eastern Cape Department of Health, from the perspective of employees. The evaluation report has three sections that are designed as interrelated but stand-alone documents. Section One is written as a report directed to the Eastern Cape Department of Health. Section Two is a review of the relevant literature that was conducted to review the existing literature related to the application of performance management and development systems, and underpinned the construction of the questionnaire. Section Three provides a description and justification of the design of the research, as well as describing the research procedure followed. Pertinent components of Sections Two and Three are extracted from these sections and included in the report in Section One. The literature review focused on the following areas: the purpose of performance management, components of the performance management process, challenges/ criticism of performance management systems, integration of performance management with other systems and the effectiveness of performance management system. The results revealed that about 74% of employees disagree that management is committed towards the successful application of the performance management system. This finding concurs with the literature. For example, De Waal and Counet (2009:367) argue that one of the problems in the application of performance management system is that the management lacks commitment to the implementation of a performance management system. Systematic sampling (Leedy and Ormrod, 2010) was used to select 120 participants in three Departmental programmes or clusters from grade levels six to 15. The researcher distributed the questionnaires to every fifth person of the population electronically using SurveyBob, which is an on line survey tool. The collected data was then analyzed using Excel software. The findings indicated that although overall employees are not satisfied with the application of the PMDS system in the Eastern Cape Department of Health, there were some successes. Nevertheless, the challenges outweighed successes of the system. The challenges that resulted in the failure of the system include poor communication, a lack of understanding of the system by the employees and a lack of knowledge with regards to the integration of PMDS with other initiatives and plans already in place. Page 4 There were positive views with enabling factors and these were work plans that are mutually agreed upon between the employee and their supervisors and are aligned to departmental strategic priorities. Constraining factors included the low levels of commitment of the management to the application of the PMDS processes, review meetings not being undertaken on a quarterly basis, and a lack of written outcome reviews. The majority of the study participants believe that the PMDS lacks fairness in its implementation. Recommendations were made on the basis of the gaps that were identified so as to improve the application of the performance management system in the Eastern Cape Department of Health. It is therefore recommended that the Department should ensure that training and development of employees on the PMDS takes place to enhance manager's understanding of the policy. This will enable managers to understand the important role played by performance management in their day to day activities. A performance management and development system needs to be integrated with all other processes to be effective. On-going communication of the PMDS policy should be considered. Accountability of managers to the Accounting Officer and submission of quarterly reports are imperative to ensure their compliance. In conclusion, dissatisfaction outweighs satisfaction of the employees with regards to the implementation of the PMDS system.
Keywords: Eastern Cape (South Africa) -- Department of Health -- Management Performance -- Management Personnel management -- South Africa; Eastern Cape Health Department